Analisis Pengaruh Indeks Pembangunan Manusia dan Keuangan Digital terhadap Pertumbuhan Ekonomi - Eka Siburian; Meilany Dwi; Reneva Manurung; Risa Nabila; Dodi Siburian; Nasrullah Hidayat (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This research discusses panel data regression models on the Human Development Index (HDI) and digital finance in Indonesia during the 2019-2023 period. The secondary data used in this research is a combination of time series data from 2019- 2023 and cross section data covering 34 provinces in Indonesia. This data was obtained from the Central Statistics Agency (BPS) and Bank Indonesia. The research began by determining the best panel data regression model using the REM (Random Effect Model) approach. The research results show that the HDI variable has a positive influence on economic growth, while digital finance has a negative influence on economic growth. Simultaneous tests show that overall, HDI and digital finance do not have a significant influence on economic growth.